Pengembangan Strategi Pemasaran Ekonomi Kreatif di Kalangan Mahasiswa (Studi Kasus: Pemasaran Buket) - Alwan Isya Alkhoezuri; Eny Siskawati; Naeli Fatikha; Very Alfi Farchina; Sri Mumaeni Agustina (Journal Economic Excellence Ibnu Sina, 2023)
The creative economy is a growing and promising sector in Indonesia. However, this development cannot be separated from the role of an effective marketing strategy in marketing the products and services it produces. Students are one of the potential consumer segments of the creative industry. The creative economy of bouquet marketing among students is useful for honing certain talents, skills and creativity from the community to provide welfare and increase pocket money. This study uses a descriptive qualitative method, namely by explaining bouquet marketing as a developer of creative economic marketing strategies among students in a narrative form. Students consider the creative economy as a place that has great potential and opportunities. They see that creative industries such as art, design, music, film, fashion, and computer games can produce innovative works and create new jobs. In addition, the creative economy is considered as a space where one can express their creativity freely. The marketing strategy used by students to promote their business is to use social media such as WhatsApp, Instagram and others. There are several strategies for online marketing that might attract potential customers. Among them is using attractive pictures or videos, visuals are very important in attracting the attention of online consumers. The suggestion is to promote more often, create more so that customers are interested.